2001
DOI: 10.1111/j.1745-3992.2001.tb00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Teachers' Classroom Assessment and Grading Practices

Abstract: What variables d o secondary teachers use t o assign grades? What is the relationship between classroom assessment practices and grading? 1s the form of classroom assessment related to grade level, subject area, and student ability? James H. McMillan is a Professor at the School of Education, Virginia Commonwealth UniversiCy, Box 84.2020, Richmond, VA 23284-2020. His specializations are educational research, educational measurement, and classroom assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
194
2
18

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(231 citation statements)
references
References 13 publications
17
194
2
18
Order By: Relevance
“…Jest możliwe, że stopnie odzwierciedlają także istotne z punktu widzenia skuteczności nauczania czynniki o charakterze pozapoznawczym (Ekstrom, 1994;Brookhart, 1997;McMillan, 2001;Rakoczy, Klieme, Bürgermeister i Harks, 2008;Randall i Engelhard, 2010) Zdaniem niektórych badaczy stopnie szkolne są raczej miarą spełniania wielowymiarowego standardu "dobrego ucznia" niż miarą jego osiągnięć w zakresie danego przedmiotu szkolnego (Kimball, 1989;Allen, 2005;Mullola i in., 2012;Spilt, Koomen i Jak, 2012). Ponieważ bliżej tego standardu są uczennice, to tłumaczy ich wyższe oceny.…”
Section: Międzypłciowe Różnice Nauczycielskich Ocen Osiągnięć Uczniówunclassified
“…Jest możliwe, że stopnie odzwierciedlają także istotne z punktu widzenia skuteczności nauczania czynniki o charakterze pozapoznawczym (Ekstrom, 1994;Brookhart, 1997;McMillan, 2001;Rakoczy, Klieme, Bürgermeister i Harks, 2008;Randall i Engelhard, 2010) Zdaniem niektórych badaczy stopnie szkolne są raczej miarą spełniania wielowymiarowego standardu "dobrego ucznia" niż miarą jego osiągnięć w zakresie danego przedmiotu szkolnego (Kimball, 1989;Allen, 2005;Mullola i in., 2012;Spilt, Koomen i Jak, 2012). Ponieważ bliżej tego standardu są uczennice, to tłumaczy ich wyższe oceny.…”
Section: Międzypłciowe Różnice Nauczycielskich Ocen Osiągnięć Uczniówunclassified
“…An accumulation of research showed that teachers' grading practices not only diverged from the recommendations of measurement specialists, they also varied considerably across teachers and were sometimes inconsistent even within a teacher's own practice (Anders & Richardson, 1992;Brookhart, 1993;1994;Cross & Frary, 1996;Friedman & Troug, 1998). McMillan (2001) surveyed teachers in the United States (n=1,483) and confirmed that the "hodgepodge" (Brookhart, 1991, p. 36) nature of grades and grading practices had continued into the 21 st century. Duncan and Noonan (2007) built on McMillan's (2001) work and surveyed secondary teachers (n=513) within the context of assessment reform in Saskatchewan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…McMillan (2001) surveyed teachers in the United States (n=1,483) and confirmed that the "hodgepodge" (Brookhart, 1991, p. 36) nature of grades and grading practices had continued into the 21 st century. Duncan and Noonan (2007) built on McMillan's (2001) work and surveyed secondary teachers (n=513) within the context of assessment reform in Saskatchewan. Their findings were consistent with previous research in that the teachers' practices varied by subject-area, and non-achievement factors were frequently included in the calculation of students' grades.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These deep questions are the sort of open-ended queries that require deep thinking and recall rather than a rote response, that span significant amounts of content rather than a single sentence. Unsurprisingly, it is these deep questions that have the greatest educational value (Anderson, 1975;Andre, 1979;McMillan, 2001). They are thus a key assessment mechanism for a spectrum of online educational options, from MOOCs to interactive tutoring systems.…”
Section: Introductionmentioning
confidence: 99%